Ars Erotica: Sex and Somaesthetics in the Classical Arts of Love: Exploring Shusterman’s Writing Identity in the Discourse on the Art of Lovemaking and Body Aesthetics - Setiono Sugiharto (Universitas Sanata Dharma, 2024)
Standing in marked contrast with Foucauldian notion of “the care for the self” which seeks bodily pleasure by advocating violent practices of consensual homosexual sadomasochism and drugs, Shusterman’s Ars Erotica takes up the notion further by unveiling the idea of somaesthetics that alternatively favors such tranquil, less violent somatic practices as a pursuit of bodily pleasure and cultivation. Rich in its cross-cultural perspectives of how artistic body practices (including the art of love making) are cultivated, Ars Erotica combines important ideas from different philosophical traditions with literary works emanating from varied cultural, religious, and linguistic legacies. The mixture of both philosophy and literature in the book helps reconcile the long-standing disputes regarding the divide between the two scholarships, thus making Shusterman’s writing worthy of investigating. Drawing on these notions of aspects of identity – “self as author” and “discoursal self” (Ivanic, 1998), this article is an attempt to explore these aspects of identity. Thematic coding was used as a technique of data analysis. Findings revealed that aspects of identity can be categorized and suggested as follows: (1) taking control by evaluating while averring to reliable sources, (2) interfering credible sources by infusing personal positioning (3) translanguaging to create aesthetic textual postures.